ANALISIS KUALITAS PELAYANAN JASA KESEHATAN PADA RUMAH SAKIT IBU DAN ANAK ERIA BUNDA PEKANBARU - Rahman Saputra; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The problem in this research is still a lack of service perceived by the patient as the length of time to wait for the desired patient's physician, the incompatibility of room facilities with costs to be incurred by the patient and a decrease in the number of inpatients and the value of existing BOR performing hospitals still not ideal. The purpose of the study is to determine and analyze the quality of health services at the Mother And Child Hospital Eria Bunda Pekanbaru, and to know the inhibiting factors in the quality of health services at the Mother And Child Hospital Eria Bunda Pekanbaru. The study concluded that health services in the Mother And Child Hospital Eria Bunda Pekanbaru which includes an tangibles, reliability, responsiveness, assurance and empathy, where health services the Mother and Child Hospital Eria Bunda Pekanbaru overall good. Nevertheless there are still shortcomings perceived by consumers. While the inhibiting factors of health services at the Mother and Child Hospital Eria Bunda Pekanbaru is still a lack of qualified doctors remain, particularly obstetricians in Mother and Child Hospital Eria Bunda Pekanbaru, physical facilities in the rooms of hospitalization, especially for room in class I, II and III, are still using the old stuff and the absence of facilities like television, room for classes II and III were deemed sufficiently narrow with 2 to 3 beds and air-conditioning that is only one piece, thus making the room feel heat, the difference in care for patients with President Suite and VIP rooms with patients in class I, II and III. Keywords: services, health services, rsia eria bunda